Synthesis of the C1–C12 Fragment of Calyculin C - Konstantinova, Olga V.; Koskinen, Ari M.P. (Synthesis, 2019)
Calyculins are a class of highly cytotoxic metabolites originally isolated from the marine sponge Discodermia calyx. To date, a total of twelve different calyculins (A–J) and calyculinamides (A, B and F) have been described, the most abundant (in D. calyx) being calyculins A and C. Herein, we demonstrate a concise route to access the C1–C12 tetraene fragment of calyculin C using transition-metal-catalyzed coupling reactions (Suzuki–Miyaura, Stille, Negishi and Heck) for the key connections. The synthesis starts from propionaldehyde and proceeds in 10 steps with 7.5% overall yield. We also describe an efficient route for the preparation of (Z)-3-iodobut-2-enenitrile in four steps and 68% yield.
Keywords: calyculins; natural products; transition-metal-catalyzed cross-coupling; Suzuki–Miyaura; Stille; Negishi and Heck coupling; syntheses of di- and polyenes